2004
DOI: 10.1097/01.mlg.0000149455.68135.de
|View full text |Cite
|
Sign up to set email alerts
|

Microtia Chondrocytes as a Donor Source for Tissue‐Engineered Cartilage

Abstract: Objectives/Hypothesis: Current surgical techniques for the correction of microtia are challenging. Research in the field of tissue engineering is providing insight into chondrocyte behavior for a possible future treatment of microtia. The authors wished to evaluate the biological potential of chondrocytes isolated from microtia cartilage as compared with normal auricular cartilage as a source of tissue-engineered cartilage. Study Design: A comparative research design to study the potential of microtia cartilag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
35
0
4

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(39 citation statements)
references
References 12 publications
0
35
0
4
Order By: Relevance
“…Kamil et al . () first reported that microtia ear chondrocytes could form robust cartilage tissue similar to native. Yanaga et al .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Kamil et al . () first reported that microtia ear chondrocytes could form robust cartilage tissue similar to native. Yanaga et al .…”
Section: Introductionmentioning
confidence: 99%
“…Notably, for microtia patients the remnant ear that commonly discarded during surgery has become a valuable cell source for cartilage tissue regeneration. Kamil et al (2004) first reported that microtia ear chondrocytes could form robust cartilage tissue similar to native. Yanaga et al (2009) developed a two-stage method using chondrocytes derived from remnant ear compounded with hydrogel to regenerate cartilage tissue for treating human microtia.…”
Section: Introductionmentioning
confidence: 99%
“…Autologous chondrocytes isolated from normal or microtia cartilage will be utilized as the donor source for the generation of human tissue-engineered cartilage for neo-auricular constructs [1][2][3][4][5]. Only a limited supply of donor cartilage is available, yet the generation of a large number of new cells in a practical time limit will be required.…”
Section: Introductionmentioning
confidence: 99%
“…Genetic and morphologic differences of elastic chondrocytes between normal auricle and microtia have not been clarified. Tissueengineered cartilage formation by microtia chondrocytes also showed similar elastic features of normal auricular chondrocytes [13]. Thus, cells isolated from autologous cartilage are definitely ideal for repair that also prevents immune rejection and transmittable disease.…”
Section: Introductionmentioning
confidence: 72%